Sterilization Resistance of Bacterial Spores Explained with Water Chemistry - Friedline, Anthony W; Zachariah, Malcolm M; Middaugh, Amy N; Garimella, Ravindranath; Vaishampayan, Parag A; Rice, Charles V (The journal of physical chemistry. B, 2015)
Bacterial spores can survive for long periods without nutrients and in harsh environmental conditions. This survival is influenced by the structure of the spore, the presence of protective compounds, and water retention. These compounds, and the physical state of water in particular, allow some species of bacterial spores to survive sterilization schemes with hydrogen peroxide and UV light. The chemical nature of the spore core and its water has been a subject of some contention and the chemical environment of the water impacts resistance paradigms. Either the spore has a glassy core, where water is immobilized along with other core components, or the core is gel-like with mobile water diffusion. These properties affect the movement of peroxide and radical species, and hence resistance. Deuterium solid-state NMR experiments are useful for examining the nature of the water inside the spore. Previous work in our lab with spores of Bacillus subtilis indicate that, for spores, the core water is in a more immobilized state than expected for the gel-like core theory, suggesting a glassy core environment. Here, we report deuterium solid-state NMR observations of the water within UV- and peroxide-resistant spores from Bacillus pumilus SAFR-032. Variable-temperature NMR experiments indicate no change in the line shape after heating to 50 °C, but an overall decrease in signal after heating to 100 °C. These results show glass-like core dynamics within B. pumilus SAFR-032 that may be the potential source of its known UV-resistance properties. The observed NMR traits can be attributed to the presence of an exosporium containing additional labile deuterons that can aid in the deactivation of sterilizing agents.